WHAT IS LEXICOLOGY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
ABSTRACT: Lexicology is the branch of linguistics that studies the nature, meaning, and structure of words. It encompasses various aspects of vocabulary, including word formation, semantic relationships, and the evolution of words over time. This field examines how words function within a language, their usage in different contexts, and their connections to cultural and social factors. Lexicology also explores the organization of words in dictionaries and the principles underlying lexical databases. By analyzing the intricacies of vocabulary, lexicology contributes to our understanding of language development, communication, and cognitive processes related to language use.